Ods herreds ejendomme på reformationstiden - Ulsig, Erik (Historisk Tidsskrift, 2013)
Property Ownership in the Odsherred 1536A hundred years ago the historian Kristian Erslev wrote that the church and the nobility in Denmark at the end of the Middle Ages each owned thirty-five to forty per cent of the holdings in Denmark, while the remaining twenty-five percent was divided between the crown and the propertied peasants. On the whole his estimate is still accepted. But several subsequent studies of local conditions have demonstrated great variation from one part of the country to another and from one locality to another. In the case of Zealand, in particular, it is possible to reconstruct the distribution of ownership rather precisely. The basis for this is the large number of cadastres stemming from the second half of the sixteenth century. These ledgers record the estates of the crown and freeholders, including the lands that were taken from the bishops and monasteries during the Danish Reformation in 1536. In the case of the ecclesiastical institutions that survived after 1536 their cadastres as well as their letters of acquisition contain property lists. Information on the lands of the nobility is, on the contrary, tenuous, but what was owned by neither crown nor church was eo ipso owned by the nobility. To determine its extent it is necessary to know how many holdings there were. The source material is sufficiently ample to be certain that changes regarding the number of holdings on Zealand were minimal into the seventeenth century, where their number is known village by village.On the other hand, the distribution of ownership between the various social orders (stænder) underwent a number of changes between 1536 and the earliest extant cadastre. The crown’s letters of acquisition from around 1536 onwards are, however, extant and published in Kronens Skøder (Crown Deeds); the collection is so complete that it is possible to trace every property transaction, above all, the numerous exchanges between the nobility and the crown, including the surviving ecclesiastical institutions, in the second half of the sixteenth century. As a result, one can reconstruct the extent and location of the properties belonging to the crown/church and the nobility at the time of the Reformation.Once this is done, the problem is to sort out what the crown owned before the Reformation and what it subsequently derived from the church. The task is readily accomplished in the case of Sømme district around Roskilde, since an extant cadastre from 1554 distinguishes sharply between crown and episcopal properties prior to the Reformation. Cadastres and letters held by the three rich convents in Roskilde are also extant. The matter is more difficult in the case of the district of Odsherred, where the Dragsholm cadastre goes no further back than 1591/92. The object of the present study is to reconstruct the distribution of property of that district in 1536.The property distribution of the district around 1591 is presented in Table 1. At that time the crown owned close to all the properties: six hundred and ninety- six peasant holdings out of seven hundred and fifty-two. The number of farms recorded in the earliest land register from 1664 was virtually the same, seven hundred and fifty, confirming that we know of virtually all the holdings from about 1591. Both lists include some smallholders, but not cottagers. In 1591 the nobility owned only six holdings. Fortunately, the Danish National Archive is in possession of a list of estates owned by the nobility in Odsherred in 1553, a document that was apparently composed because the king wished to acquire (through exchange) all nobility property in the district to secure royal hunting rights. It was a matter of a total of one hundred and nineteen holdings, and by utilizing the Kronens Skøder collection it can be ascertained that subsequently the crown did systematically acquire the properties in question. Furthermore, the 1553 list and a monastic cadastre show that nobles had acquired thirty-four of the hundred and nineteen holdings from monasteries. The lands owned by the nobility in 1536 consisted, therefore, of only eighty-five holdings (see Map 2).The main analysis deals with the Dragsholm cadastre from 1591. It bears numerous traces of the composite origin of its holdings. In regard to certain holdings it relates that some were once subservient to Kalundborg and some to Dragsholm. In 1591 all the peasants were, of course, subservient to Dragsholm, but as we know from its previous history, Odsherred was transferred from Kalundborg to Dragsholm, when the latter was elevated to a superior district (hovedlen) in 1566. To all appearances the only properties belonging to Dragsholm before 1566 were the extensive episcopal estates in Odsherred and the areas south of it, while the castle of Kalundborg possessed Odsherred’s medieval crown lands, the district’s previous monastic estates, and the lands it acquired there from the nobility. The cadastre of 1591 (and its unknown antecedents) must therefore be the product of combining two older cadastres, which had existed in 1566. A close examination does, indeed, reveal distinct traces of such a compilation. In particular, there is a striking difference between the common duties on peasant plots: cows or cattle from those subservient to Dragsholm, but so-called "young cattle money" (nødeskat) paid by many previously subservient to Kalundborg. There were also differences between the duties on individual holdings, e.g., only those previously subservient to Kalundborg could fulfil their progress obligations with barley or money instead of barley. Generally speaking, the system of payments had been firmly established by the end of the Middle Ages, and the 1664 land register shows that all the holdings known in 1591 were still bound by the same duties.The analysis of peasant duties tells us who previously owned the great majority of holdings in Odsherred. It is of particular interest that the pattern of duties identifies sixty holdings that had belonged to the Convent of Our Lady in Roskilde, a complex of lands whose size and location is otherwise unknown (see Map 2).However, besides the village of Rørvig, where the crown between 1566 and 1591 gave all twenty-four holdings equal status (and thus deleted every trace of former relations), the previous status of over one hundred holdings still remains to be established. But a re-examination of the 1591 cadastre reveals that the old Dragsholm holdings are always listed first in villages where there were other owners. The bishop, of course, did not have holdings in every village, but a look at the cadastre’s topographical order reveals the key to the final solution of the problem. Within each parish the village with the church naturally tops the list, while the following entries are topographically random, because the villages with episcopal holdings come first. The topographical situation is illustrated in Map 3. There is only one instance of deviation from the described pattern, namely, village no. 13 in Højby Parish, which was old episcopal property. On the face of it, its position in the cadastre looks like a mistake, but, in fact, Ellinge until 1566 had been a small independent manor and had not belonged under Dragsholm.When the unknown author of the 1566 cadastre was faced with the task of compiling the entries of two older cadastres into a single new document, he chose an understandable and logical procedure, which was also the surest method of carrying out an extensive undertaking. His resultant work has provided a basis for determining the distribution of property in 1536. The bishopric possessed two hundred and forty-one holdings, the crown two hundred and forty-five, the monasteries ninety-eight, the nobility eighty-five, the Roskilde cathedral chapter twenty-one, churches and clerics twenty-four, and the Vartov hospital five. The only undetermined properties are the twenty-four Rørvig holdings and three holdings in and around Asminderup parish.The correctness of the analysis can be confirmed by examining the cadastre of the Bishop of Roskilde from 1370-95. Data on the extent and position of crown and episcopal lands were on the whole still valid in 1536, although frequent changes had occurred in the structure of the holdings, and nearly always changes regarding duties.Translated by Michael Wolfe